Experimental Investigation of Flame Stability in the Premixed Propane-Air Combustion in Two-Section Porous Media Burner - Bubnovich, V; Flores-Salinas, C; Flores-Salinas, C (Elsevier Ltd, 2021)
The characteristics of combustion and the flame stabilization within a two-layer porous media burner were investigated experimentally in the present study. Lean propane-air mixtures were used with the equivalence ratio values ϕ in the range between 0.1 and 0.5 and the flow rate Q of the mixture in the range between 10 and 45 l/min. It was experimented with three porous ceramics: reticulated foam alumina, honeycomb foam alumina and SiC foam. The axial temperature distribution, reaction zone, maximum temperature, CO and NOx emissions, and combustion wave propagation rate were analyzed. The experimental results showed that, in the three ceramics studied, the combustion wave propagation rate increases with increased inlet velocity and decreased equivalence ratio of premixed gases. Result of the analysis of the information obtained, a porous burner with flame stabilized between two porous ceramics was built that works permanently with the equivalence ratio ϕ = 0.5 and the flow rate of the mixture in the range between 20 and 35 l/min. The honeycomb foam was placed on top of the burner and the reticulated foam on the bottom. The combustion temperatures were in the range between 1160 and 1380 K, where a higher flow rate resulted in higher temperatures. The CO and NOX emissions did not exceed a few ppm showing that combustion was almost complete. © 2021 Elsevier Ltd